Bonsai Sebagai Ide Karya Seni Lukis Surealistik - Imroni Imroni; Yasrul Sami (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This work aims to visualize various issues related to insomnia. It reflects the author's concern about how insomnia disrupts human activity and physical health. The creation of this artwork explores how to translate the concept of insomnia into figurative abstract painting. The methods and processes used in creating this abstract figurative artwork involve several stages: (1) Preparation, (2) Elaboration, (3) Synthesis, (4) Concept Realization, and (5) Completion. The technique employed is acrylic on canvas. The result of this work, visualized on a two-dimensional medium, has led to the development of titles such as “Keseimbangan” (Balance), “Kasih Sayang” (Affection), “Dedikasi Orang Tua” (Parental Dedication), “Pilihan” (Choice), “Cinta Pertama” (First Love), “Kampak Pertahanan” (Defense Axe), “Pistol Kehidupan” (Life Pistol), “Rumah Rantau” (Home Away), and “Sajian Bonsai” (Bonsai Presentation).